Simultaneous Elections in North Aceh Regency: An Islamic Perspective - Nasrullah Arull Yahya (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
The 2019 Simultaneous Regional Election has brought about some problems which threaten the quality of local democracy, especially in North Aceh Regency, Indonesia. The research aims at discussing the practice of regional election in North Aceh Regency from Islamic perspective. In Islamic law, the implementation of elections is carried out in accordance with the principles of justice and equal rights. This research is a normative and empirical study, where the research data is obtained through library research and interviews with informants. While the data analysis used is descriptive analysis. The results show that the problems in the implementation of the 2019 simultaneous elections in North Aceh Regency according to Islamic law were; first, there is a question on neutrality of the Election Commission officers in carrying out its duties and functions, such as taking sides to certain candidates or parties by way of inflating votes. This is contrary to the principles of Islamic law, namely the principles of justice and equal rights; Second, the weakness of human resources in operating computers for inputting voter data and election result data. In Islamic law, the lack of qualified human resources has an impact on the inability to account for the mandate as caliph; and third, the inadequate facilities and infrastructure, both for offices (workspaces, desks, computers, and other supporting equipment) and non-available official vehicles. This situation is contrary to objective of Islamic law, namely maqashid sharia, such as essential element of life (dharuri), complementary element of life (haji) and accessories of life (tahsini) needs.